A flexure-capacity design method and seismic fragility assessment of FRP/steel double-reinforced bridge piers. Issue 9 (1st September 2020) - Jia, Daoguang; Mao, Jize; Guo, Qingyong; Yang, Zailin; Xiang, Nailiang
Abstract: Lack of post-yield stiffness and corrosion resistance could inevitably result in a considerable loss of seismic performance for steel reinforced concrete (RC) piers. Fibre reinforced polymer (FRP) reinforcement can provide high tensile strength and protection from corrosion. To achieve a better post-yield stiffness and durability for piers, FRP/steel double-reinforced configurations were designed by the proposed flexural-capacity design method. A seismic fragility assessment was also conducted to investigate the effectiveness of design parameters, namely the ultimate tensile strength of FRP reinforcement, elastic modulus of FRP reinforcement, and ratio of steel reinforcement for a double-reinforced configuration to that for a steel RC configuration ( ρ steel / ρ prototype ). The results demonstrated that the FRP/steel double-reinforced piers satisfied the mentioned objectives, while the fragility of these piers was a 30.2% less than that of conventional steel RC piers. A 79.9% higher median PGA at the collapse damage state was achieved, when the elastic modulus of FRP reinforcement changed from 164 to 80.7 GPa. An increase in the median PGA of 34.8% can be achieved along with the increase of the ultimate tensile strength of FRP reinforcement. When ρ steel / ρ prototype was approximately 66%, FRP reinforcement exhibited the highest effectiveness on the seismic performance of piers.